How to control the spatiotemporal spread of Omicron in the region with low vaccination rates - Tong, Chengzhuo; Shi, Zhicheng; Shi, Wenzhong; Zhang, Anshu (Frontiers in Public Health, 2022)
How to effectively control the spread of Omicron in regions with low vaccination rates, is an urgent issue. A district-level prediction model of COVID-19 symptom onset risk is proposed to explore to control such a whole-process spread of Omicron, in South Africa at a finer spatial scale. It has been found that i) In the early stage of accelerated spread, Omicron spreads rapidly from those districts at the center of human mobility to other important districts of the human mobility network and its peripheral districts. In the subsequent contraction-diffusion stage, Omicron has been found to dissipate rapidly in districts with low human mobility, and then mainly contracted to districts with the highest human mobility. ii) 10 times daily vaccination rates mainly reduced the onset risk of remote areas with low human mobility. if Alert level 5 in the 3 districts at the epicenter, and Alert level 1 in the remaining 49 districts was further incorporated, the spatial spread related to human mobility could be effectively restricted, and the daily onset risk in districts with high human mobility also decreased by 20% - 80%.